Current Diagnosis and Management of Helicobacter pylori - Nikko Darnindro; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2013)
Helicobacter pylori (H. pylori) is a microbe which cause chronic infection in human. Currently, the prevalence in developed countries continue to decrease, but the same does not happen in developing countries. Orofecal transmission and its connection with environmental condition is assumed to be its cause.Impact of H. pylori infection in gastric mucosa is influenced by the bacteria pathogenesis which is able to survive in acid condition and causes inflammatory reaction. The diagnosis is differentiated through endoscopy or non-endoscopy depends on the alarm symptoms, local prevalence, pre-test probability, availability, cost and aim of examination.Management of H. pylori depends on the high rate of clarithromycin resistence. In area with resistency prevalence below 20% triple therapy can still be used, while in increasing resistency area, use of four times daily therapy or other antibiotics such as levofloxacin and furazolidone can be considered.Keywords: Helicobacter pylori, diagnosis, alternative therapy